AFM characterization of surface mechanical and electrical properties of some common rocks - Tian, Xianghui; He, Xueqiu; Song, Dazhao; Li, Zhenlei; Khan, Majid; Liu, Huifang; Qiu, Liming (International journal of mining science and technology, 2022)
The characterization of micro-surface mechanical and electrical properties of the natural rock materials remains inadequate, and their macroscopic performance can be better comprehended by investigating the surface properties. With this purpose, the present research focuses on characterizing the micro-surface morphology, Derjaguin-Muller-Toporov (DMT) modulus, adhesion, and potential of granite, shale, and limestone by employing the atomic force microscope (AFM) as a pioneer attempt. The results show that the micro-surface morphology of the rock fluctuates within hundreds of nanometers, among which the granite micro-surface is comparatively the smoothest, followed by limestone. The morphology of the shale is the roughest, indicating that the regional difference of shale micro-surface is dominant. The distribution of the adhesion on rock micro-surface is uneven; the average adhesion of eight measuring areas for shale is 23.93 nN, accounting for three times of granite and limestone, while the surface DMT modulus of shale is relatively lower than granite and limestone. It is inferred from the obtained results that higher surface adhesion is helpful to the gas adsorption of shale, and the lower surface DMT (elastic) modulus is useful to the formation of fractures and pores. Thus, these two are the micromechanical basis of shale gas adsorption. Additionally, introducing a method to reduce the surface adhesion will benefit the exploration of unconventional resources such as shale gas. The micro-surface of the three types of rocks all shows electricity, with average potential ranging from tens of millivolts to hundreds of millivolts. Besides, the micro-surface potential of the rocks are heterogeneous, and both positive and negative points can be found. The existence and uneven distribution of micro-surface potential provide a robust physical basis for the electromagnetic radiation generated by rock fracture under loading. This study offers a new method for revealing the adsorption characteristics of unconventional gas reservoir rocks and the electromagnetic radiation mechanism of the rock fracture.